Congenital Basal Meningocele: An Unusual Cause of Nasal Obstruction in Early Life - Retnaningtyas, Lucia Pudyastuti (Keluwih: Jurnal Kesehatan dan Kedokteran, 2025)
Abstract— Basal meningoceles are rare congenital defects that can cause nasal obstruction and often clinically occult until they result in life-threatening complications. Knowing the clues to early diagnosis, management, and complications is essential. Case: A 7-day-old baby girl was referred to our hospital because of high fever and dyspnoea, and the baby was diagnosed with pneumonia, lip tie, cup ears and suspicion of laryngomalacia. The patient got dyspnoea with stridor when drinking, and it decreased when her mouth was open. The suction catheter could not enter through the left choana. The nasal endoscopy showed an elevation of the hard palate. A 3-dimensional facial CT scan demonstrated a transsellar–transsphenoidal meningocele protruding into the left nasal cavity. A diluted liquid came out from the left nose with a yellowish-clear colour, and the baby showed a high-pitched cry. Bacterial meningitis was established from cerebrospinal liquor analyses. After meningitis treatment, surgical repair to meningocele reposition and bone defect repair was done at 40 days. Conclusion: In our case, the nasal obstruction was not detected from the beginning of birth, and it led to delays in finding the cause. Basal meningocele in this case was accidentally diagnosed by a facial CT scan exploring the cause of choana atresia. It’s essential to detect choana atresia since birth, explore the etiology immediately, and manage it well to prevent life-threatening complications. Keywords: nasal obstruction, congenital basal meningocele Abstrak—Meningocele basal merupakan kelainan kongenital langka yang dapat menyebabkan obstruksi hidung yang secara klinis sering tersembunyi sehingga baru diketahui saat sudah terjadi komplikasi. Oleh karena itu sangat penting untuk mengetahui cara menegakkan diagnosis dini agar dapat diberi tata laksana yang tepat untuk mencegah terjadinya komplikasi yang mengancam nyawa. Kasus: Seorang bayi perempuan berusia 7 hari dirujuk ke rumah sakit kami karena demam tinggi dan dispnoea dan bayi itu didiagnosis sebagai pneumonia, ikatan bibir, telinga cangkir dan kecurigaan laringomalesia. Pasien mengalami dispnea dengan stridor saat minum; dan menurun ketika mulutnya terbuka. Kateter hisap tidak bisa masuk melalui choana kiri. Endoskopi hidung menunjukkan peningkatan langit-langit keras. CT scan wajah 3 dimensi menunjukkan transsellar – meningocele transsphenoidal yang menonjol ke dalam rongga hidung kiri. Cairan encer keluar dari hidung kiri dengan warna bening kekuningan, dan bayi itu menunjukkan tangisan nada tinggi. Meningitis bakteri ditetapkan dari analisis cairan serebrospinal. Setelah meningitis diobati, perbaikan bedah reposisi meningocele dan perbaikan cacat tulang dilakukan pada usia 40 hari. Kesimpulan: Dalam kasus kami, meningocele basal secara tidak sengaja didiagnosis dengan CT scan wajah yang mengeksplorasi penyebab choana atresia. Sangat penting untuk mendeteksi choana atresia sejak lahir, segera mengeksplorasi etiologinya, dan mengelolanya dengan baik untuk mencegah komplikasi yang mengancam jiwa. Kata kunci: obstruksi hidung, meningocele basal kongenital